Digital cameras derived raster image transformation of old map sheets - Soycan, Arzu (ACADEMIC JOURNALS, 2010)
The main focus of the research is to obtain digitized old map sheets with high geometric accuracy ( a few decimeters of error) for Geographical Information Systems, urban planning, surveying engineering and other applications. For this purpose, Portable Digital Camera Raster Image versus Scanner Raster Image is examined regarding their use in reproduction of old map sheets in Digital Vector Map format. Therefore, we focused on coordinate transformations between the raster and the spatial coordinate systems along the research. The transformation methods subjected to this research are the Helmert, Affine, Polynomial transformations and radial basis functions techniques. Accordingly, a case study was performed on the 1/1000 scaled map sheets were the raster images are gathered using a portable digital camera and scanner. The performance of the results obtained by fitting techniques based on radial basis functions namely multiquadrics, natural cubic spline, thin plate spline and third order polynomials gave successful solutions according to this procedure. Root Mean Square error of the Scanner Raster Image for dx differences are 0.180, 0.183, 0.224, and 0.339 m and the Root Mean Square of the dy differences are 0.167, 0.223, 0.240, and 0.379 m, respectively for thin plate spline, natural cubic spline, multiquadrics and third order polynomials models. Similarly, Root Mean Square error of the Portable Digital Camera Raster Image for dx differences are 0.173, 0.176, 0.225, and 0.352 m and the Root Mean Square of the dy differences are 0.196, 0.240, 0.264, and 0.365 m respectively for thin plate spline, natural cubic spline, multiquadrics and third order polynomials models.
Keywords: Coordinate transformation; digital camera; radial basis functions; mapping; geographical information systems; ALGORITHM; GPS; Science & Technology - Other Topics